Information Logistics for Supply Chain Management within Process Industry Environments - Vegetti, Maria Marcela (2005)
This contribution proposes the design of an ontology that provides the foundations for the specification of information logistics processes in extended supply chains associated to process industries. The proposed ontology includes concepts and relationships that are necessary to formally describe, measure and evaluate a supply chain (SC), thus simplifying the visualization and analysis of networks. A SC ontology is a first step towards achieving a standard description of SC design and management processes.